2018
DOI: 10.7150/ijms.22812
|View full text |Cite
|
Sign up to set email alerts
|

A FCGR3A Polymorphism Predicts Anti-drug Antibodies in Chronic Inflammatory Bowel Disease Patients Treated With Anti-TNF

Abstract: Background. The production of anti-drug antibodies (ADAs) against IgG monoclonal antibodies (mAbs) targeting tumour necrosis factor (TNF) is an important cause of loss of response to anti-TNF mAbs in patients with inflammatory bowel diseases (IBD) such as Crohn's disease (CD) and ulcerative colitis (UC). Since receptors for the Fc portion of IgG (FCGRs) are involved in the degradation of IgG complexes, we hypothesised that a polymorphism in FCGR3A (V158F; rs396991) gene could be involved in anti-TNF ADA genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 23 publications
5
29
1
Order By: Relevance
“…However, its potential functional effect and translation into clinical consequences have to be validated experimentally. In fact, the genetic amino acid substitution p.V158F (rs396991) in the FCGR3A gene, which is well described in the literature, was found to affect the response to antibodies treatment in the case of inflammatory bowel disease (Louis et al, 2004;Moroi et al, 2013;Louis et al, 2016;Romero-Cara et al, 2018). However, the association between this polymorphism and the clinical response in CD has also been questioned (Slebioda and Kmiec, 2014), and it is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…However, its potential functional effect and translation into clinical consequences have to be validated experimentally. In fact, the genetic amino acid substitution p.V158F (rs396991) in the FCGR3A gene, which is well described in the literature, was found to affect the response to antibodies treatment in the case of inflammatory bowel disease (Louis et al, 2004;Moroi et al, 2013;Louis et al, 2016;Romero-Cara et al, 2018). However, the association between this polymorphism and the clinical response in CD has also been questioned (Slebioda and Kmiec, 2014), and it is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, some of its underlying mechanisms are on a degree of overlapping or opposite to each other. 8,10 Thus, a comprehensive comparison via genetics, gene expression data, and microbe provides an excellent to investigate the molecular mechanisms of resistance to anti-TNFα agents and predictive biomarkers. [11][12][13][14][15][16][17] So far, published studies using gene expression data from intestinal or blood samples of IBD patients collected before anti-TNFα therapy have identified several signature patterns of non-response patients.…”
Section: Introductionmentioning
confidence: 99%
“… 60 As a result of clinical evidence, assessment of immunogenicity is now a mandatory requirement of the European Medicines Agency and the Food and Drug Administration prior to approval of all biological agents: 61 – 63 the ability to identify patients at increased risk of immunogenicity may influence the choice of anti-TNF treatment and the use of preventive strategies, including combination with immunomodulator. Retrospective studies have suggested that variants in FCGR3A 64 and HLA-DRB1*03 65 increase susceptibility to immunogenicity to anti-TNF therapy. These associations did not achieve genome-wide significance and are yet to be independently replicated.…”
Section: Methodsmentioning
confidence: 99%